2001
DOI: 10.1016/s0370-1573(00)00114-9
|View full text |Cite
|
Sign up to set email alerts
|

Phase fluctuations and pseudogap phenomena

Abstract: This article reviews the current status of precursor superconducting phase fluctuations as a possible mechanism for pseudogap formation in high-temperature superconductors. In particular we compare this approach which relies on the twodimensional nature of the superconductivity to the often used T -matrix approach. Starting from simple pairing Hamiltonians we present a broad pedagogical introduction to the BCS-Bose crossover problem. The finite temperature extension of these models naturally leads to a discuss… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
285
0
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 252 publications
(296 citation statements)
references
References 256 publications
(853 reference statements)
8
285
0
3
Order By: Relevance
“…In the balanced configuration n a = n b ≡ n = nT 2 . Solving these two equations selfconsistently we arrive at the well-known results [25,29] …”
Section: A Balanced Systemsmentioning
confidence: 86%
“…In the balanced configuration n a = n b ≡ n = nT 2 . Solving these two equations selfconsistently we arrive at the well-known results [25,29] …”
Section: A Balanced Systemsmentioning
confidence: 86%
“…More technical details are given in the Appendix. The T-matrix scheme adopted here was first developed in the context of high-T c cuprates [32][33][34][35]. It was later applied to study the BEC-BCS crossover phenomenon in ultracold atomic Fermi gases [36].…”
Section: Modelmentioning
confidence: 99%
“…This is not a crazy idea, because it has been shown that the observed symmetry of the order parameter cannot be fitted with only the lowest harmonics of the d-wave order parameter [18,19,20,21]. Furthermore, a recent experiment with twisted Josephson junctions in the Bi-cuprates [22], is in favor of an extended s-wave order parameter, and has shown the absence of a dwave part in the order parameter.…”
Section: Discussionmentioning
confidence: 99%